2020
DOI: 10.3390/nu12030626
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid in Human Milk

Abstract: Breastfeeding is universally recommended as the optimal choice of infant feeding and consequently human milk has been extensively investigated to unravel its unique nutrient profile. The human milk lipid composition is unique and supplies specifically long-chain polyunsaturated fatty acids (LC-PUFAs), in particular, arachidonic acid (ARA, 20:4n–6) and docosahexaenoic acid (DHA, 22:6n–3). Arachidonic acid (ARA) is the most predominant long-chain polyunsaturated fatty acid in human milk, albeit at low concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 88 publications
0
22
0
2
Order By: Relevance
“…Arachidonic acid (ARA) is a precursor of eicosanoids including leukotrienes (mediators of the immune response), prostaglandins (intracellular effectors), thromboxanes (which regulate vascular tone) and endocannabinoids [57,58]. ARA is the most predominant long-chain polyunsaturated fatty acid in human milk, albeit at low concentrations compared to other FAs.…”
Section: Fatty Acids Composition In Mammals' Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…Arachidonic acid (ARA) is a precursor of eicosanoids including leukotrienes (mediators of the immune response), prostaglandins (intracellular effectors), thromboxanes (which regulate vascular tone) and endocannabinoids [57,58]. ARA is the most predominant long-chain polyunsaturated fatty acid in human milk, albeit at low concentrations compared to other FAs.…”
Section: Fatty Acids Composition In Mammals' Milkmentioning
confidence: 99%
“…It was shown that ARA plays an important role in physiological development and its related functions during early life nutrition. Therefore, ARA is an important nutrient during infancy and childhood and, as such, appropriate attention is required regarding its nutritional status and presence in the infant diet [58].…”
Section: Fatty Acids Composition In Mammals' Milkmentioning
confidence: 99%
“…Lower breastmilk DHA concentrations were observed in Pakistan, rural South Africa, Canada, the Netherlands, and France (between 0.06% and 0.14%), especially in inland regions or in developed countries, where low marine food consumption is observed [ 104 ]. A recent review reports that ARA is detected in animal and human milk, with its content being linked to maternal ARA dietary intake [ 120 ]. Interestingly, several recent works report the presence of free and esterified ARA, EPA, and DHA-derived oxylipins in human milk [ 121 , 122 , 123 ].…”
Section: Pufas and Brain Developmentmentioning
confidence: 99%
“…Overall, the mechanistic data brought by animal studies further support the need for LC PUFA for optimal brain development. Concerning post-natal periods, breast milk remains the gold standard, as it provides both ARA and DHA [ 120 ]. Concerning infant formulae, the amount of ARA and DHA to be added is still a matter of debate, as recently reviewed [ 219 ].…”
Section: Mechanisms Of Action Of Pufas On Neurodevelopmentmentioning
confidence: 99%
“…Literature data often report that n −3 fatty acids such as DHA are modulated by diet whereas n 6 fatty acids, like ARA, are not ( 28 ).…”
Section: Introductionmentioning
confidence: 99%